Antioxidant markers based TLC-DPPH differentiation on four commercialized botanical sources of Shankhpushpi (A Medhya Rasayana): A preliminary assessment - Neeraj K Sethiya; M K Mohan Maruga Raja; Shri Hari Mishra (Wolters Kluwer Medknow Publications, 2013)
Shankhpushpi is a cognition boosting traditional ayurvedic brain supplement. Convolvulus pluricaulis (Convolvulaceae), Evolvulus alsinoides (Convolvulaceae), Clitoria ternatea (Papilionaceae), and Canscora decussata (Gentianaceae) are botanical claimants of Shankhpushpi. This investigation is to focus the identification of the compound based on biological marker differentiation of four botanical claimants of Shankhpushpi for their antioxidant evaluation on thin layer chromatography (TLC) by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. A rapid TLC-DPPH method was developed to identify and differentiate four botanical claimants of Shankhpushpi in terms of presence of β-carotene, rutin, scopoletin, chlorogenic acid, and mangiferin. C. pluricaulis shows presence of scopoletin; E. alsinoides shows presence of β-carotene, scopoletin, and chlorogenic acid; C. ternatea shows presence of β-carotene, scopoletin, and rutin; and C. decussata shows presence of β-carotene, scopoletin, and mangiferin. The order, they followed, based on their antioxidant potential is β-carotene < mangiferin < rutin < scopoletin < chlorogenic acid. Antioxidants are attributed for their beneficial role in age-related cognition decline. The proposed method provides an edge in terms of identification and quantification of antioxidant constituents in a multi-component system. This method may also provide application for identification of correct plant sources used in the name of Shankhpushpi in marketed ayurvedic formulation, food supplement, and extracts.